Phoneme Training for Adult Cochlear Implant Users: A Review of the Literature and Study Protocol - Philpott, Nikki; Philips, Birgit; Tromp, Kayla; Kramer, Sophia; Mylanus, Emmanuel; Huinck, Wendy (Journal of speech, language, and hearing research, 2023)
This study describes a protocol for a novel individualized phoneme training program for adult cochlear implant (CI) users, based on individual phoneme confusion errors. The protocol is underpinned by a literature review on phoneme training and a focus group with adult CI users. After a literature search, five studies were included for review and evaluation of quality and level of evidence. A focus group with experienced adult CI users ( = 7) was then conducted to gain insights into their experiences of auditory training post-implantation and recommendations for future training programs. The knowledge gained from the literature review and focus group was used as the foundation for a novel, individualized phoneme training program for adult CI users, for which the protocol is described in this study. A review of the literature shows that phoneme training in adult CI users has variable outcomes for on-task and off-task measures. Overall, the concept of individualized training relates to adaptive difficulty within training tasks and not to tailoring training content to participants' individual needs, as indicated by clinical outcomes. The focus group revealed that participants want to be able to track their training progress, have training content tailored to their individual needs, and expressed a preference for shorter training sessions. Using learnings from a literature review and focus group, this study describes a protocol for a novel, individualized phoneme training program for adult CI users. Study findings from this phoneme training program will be disseminated when available. https://doi.org/10.23641/asha.24392863.